Une ponction dans le fonds Paul Guadet : les plans de pose du revêtement de l’Hôtel Carnot, 1906-1908 - Valentin Gillet (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Previously only realised in infrastructural projects and industrial buildings, the introduction of reinforced-concrete frames in domestic and commercial architecture during the first years of the twentieth century in Paris required new solutions for the infill and the cladding of such filigree structures. One of the first answers was to infill the concrete skeletons with non-load-bearing, brickwork and clad the building with stoneware tiles. Frequently referred to in technical literature for workers but rarely conserved in archival collections, the laying plans provide information on both the design and the execution of cladded stoneware facades. As we have recently celebrated the fiftieth anniversary of the demolition of the hotel Carnot, the recent listing of Paul Guadet’s holdings stored in the Centre d’archives d’architecture du XXe siècle was the occasion to consider the plans that were used to design and apply the stoneware cladding on its façades, and which have remained unpublished to this day.